Research on multi-source application level multicast for awareness driven virtual space teleconferencing - ZHANG Xu; WU Hui-zhong (Tongxin xuebao)
Virtual space teleconferencing is a novel CSCW tool that has abroad application perspective.There is no effi-cient communication mechanism to realize virtual space teleconferencing on Internet because most of end hosts in today’s Internet have limited access bandwidth and the Internet does not support IP multicast.Adopting mesh-first and centralized strategies,a multi-source application level multicast method ESMVST for awareness driven virtual space teleconferenc-ing on Internet was devised.The research focused on ESMVST method’s application level multicast routing model VSTMMR and proposed a heuristic routing algorithm MDMM.The result of experiment shows that MDMM algorithm could reduce both algorithm’s rejection rate and data distribution trees’ maximal delay effectively,and ESMVST method is feasible.